Making Good : Creation, Creativity, and Artistry - Hart, Trevor A. (Book collections on Project MUSE., 2014)
God spoke, and all that is and all that ever will be came into existence. God alone can be called uncreated and Creator, and creation can only accomplish that which already exists within God's imagination. In Making Good, Trevor Hart argues that human creativity is always a matter of unfolding the possibilities already latent within the original creative event. Making Good contends that while humans must acknowledge the unique and incomparable dimensions of God's creative activity, the biblical theology of creation encourages rather than prohibits human creativity within a language of creation.